2015
DOI: 10.1021/acsami.5b06747
|View full text |Cite
|
Sign up to set email alerts
|

Lead-Free Piezoceramics: Revealing the Role of the Rhombohedral–Tetragonal Phase Coexistence in Enhancement of the Piezoelectric Properties

Abstract: Until now, lead zirconate titanate (PZT) based ceramics are the most widely used in piezoelectric devices. However, the use of lead is being avoided due to its toxicity and environmental risks. Indeed, the attention in piezoelectric devices has been moved to lead-free ceramics, especially on (K,Na)NbO3-based materials, due to growing environmental concerns. Here we report a systematic evaluation of the effects of the compositional modifications induced by replacement of the B-sites with Sb(5+) ions in 0.96[(K0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(79 citation statements)
references
References 53 publications
6
73
0
Order By: Relevance
“…There were small pores between the grains, which are favorable for the contact of the material with the surrounding body fluids [41]. The XRD pattern in Figure 5b revealed that KNN ceramic was in perovskite phase with orthorhombic-tetragonal phase coexistences, and the relative volume fractions (%) of the T (V T ) and O (V O ) of the two-phase coexistence in this system were calculated as 39 ± 3 and 61 ± 5, respectively, from the following equations [25,42]:V T = [I (002) T + I (200) T ]/[I (002) T + I (200) T + I (022) O + I (200) O ], V O = [I (022) O + I (200) O ]/[I (002) T + I (200) T + I (022) O + I (200) O ], where I (002) T , I (200) T , I (022) O and I (200) O are the integrated intensities of the tetragonal (002) and (200) peaks, orthorhombic (022) and (200) peaks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were small pores between the grains, which are favorable for the contact of the material with the surrounding body fluids [41]. The XRD pattern in Figure 5b revealed that KNN ceramic was in perovskite phase with orthorhombic-tetragonal phase coexistences, and the relative volume fractions (%) of the T (V T ) and O (V O ) of the two-phase coexistence in this system were calculated as 39 ± 3 and 61 ± 5, respectively, from the following equations [25,42]:V T = [I (002) T + I (200) T ]/[I (002) T + I (200) T + I (022) O + I (200) O ], V O = [I (022) O + I (200) O ]/[I (002) T + I (200) T + I (022) O + I (200) O ], where I (002) T , I (200) T , I (022) O and I (200) O are the integrated intensities of the tetragonal (002) and (200) peaks, orthorhombic (022) and (200) peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Though it possesses passable bio-response according to the research, BT piezoelectric ceramic is difficult to apply because of its poor stability of temperature, and the cytotoxicity of barium and titanium ions cannot be ignored. At present, for potassium sodium niobate, researchers are more inclined to improving the piezoelectric properties by doping antimony (Sb), tantalum (Ta), bismuth (Bi), and other elements [24,25,26,27] with a view to replace lead zirconate titanate in industrial applications. Such doped potassium sodium niobate (KNN)-based piezoelectric ceramics have little potential in the field of implant materials due to the toxicity of the dopant elements, despite the high piezoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, Raman is a traditional method to investigate the structure, which could tell the information about the internal modes associated with the NbO 6 octahedron. As Rubio‐Marcos et al reported, it is useful to study the relationship between the structures and the piezoelectric properties of KNN‐based ceramics using the Raman spectroscopy. On the other hand, it has been reported that the photoluminescence spectroscopy of trivalent europium ion (Eu 3+ ) can be used as a probe for small structural distortions caused by phase transition, which have been observed in both glasses and ceramics .…”
Section: Introductionmentioning
confidence: 99%
“…As x increased up to 0.02, the intensity of (200) PC peak was higher than that of (002) PC peak (Figure 1a), signifying the involvement of T phase. [11] ε r -T curve of the ceramics with x = 0.02 displayed a board T R-O of −40 ± 20 °C and a T O-T of 72 °C (Figure 1b), suggesting the existence of O phase. Thus, an O-T phase coexistence was deduced in the ceramics with x = 0.02 at room temperature, which was also observed in other KNN-based ceramics.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%